2017
DOI: 10.1111/jpn.12654
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical proximates of pumpkin (Cucurbitaeae spp.) and their beneficial effects on the general well‐being of poultry species

Abstract: SummaryThere is a growing need to increase productivity in poultry. Growth hormones and antibiotics have the ability to improve health, weight gain and feed efficiency in meat-producing animals. The growth-promoting antibiotics are administered to poultry to improve the general performance of the chicken. However, the use of the xenobiotic drugs in food-producing animals has been a concern and a sensitive issue of debate for several decades in the EU and many other regional blocks of the world. Consequently, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 54 publications
0
50
1
Order By: Relevance
“…Carotenoids, triterpenoids, ent-kaurane-type diterpene, and cucurbita glycosides are groups of phytochemical compounds found in pumpkins, which are classified as being important in carrying out ethnomedicinal properties in living organisms, including livestock and poultry. Besides carotenoid and c-tocopherol compounds in pumpkin positioning the fruit as one of the most nutritious foodstuffs, it is endowed with antifatigue properties based on activities observed during mice studies, reported by Achilonu et al [2]. Under favourable conditions, pumpkin seeds can produce a secondary metabolite, known as squalene.…”
Section: Nutritious Dietary Resources Derived From Pineapplementioning
confidence: 99%
See 4 more Smart Citations
“…Carotenoids, triterpenoids, ent-kaurane-type diterpene, and cucurbita glycosides are groups of phytochemical compounds found in pumpkins, which are classified as being important in carrying out ethnomedicinal properties in living organisms, including livestock and poultry. Besides carotenoid and c-tocopherol compounds in pumpkin positioning the fruit as one of the most nutritious foodstuffs, it is endowed with antifatigue properties based on activities observed during mice studies, reported by Achilonu et al [2]. Under favourable conditions, pumpkin seeds can produce a secondary metabolite, known as squalene.…”
Section: Nutritious Dietary Resources Derived From Pineapplementioning
confidence: 99%
“…e fats and oils are used as building blocks in biosynthesis of long-chain fatty acids and glycerol. Table 6 depicts the biochemical composition of selected pumpkin parts [2], while Table 7 indicates some important fatty acids derived from Cucurbita maxima seed oil [90]. In animal body cells, fats and oils play vital role of supplying large quantities of energy reserves required to maintain a stable body temperature [90].…”
Section: Nutritious Dietary Resources Derived From Pineapplementioning
confidence: 99%
See 3 more Smart Citations